Pengaruh Kompetensi Kepribadian Guru PAI terhadap Akhlak Siswa Setingkat Sekolah Menengah Atas - Nur Fais Zalillah; Didit Darmawan (Lembaga Pengembangan Kinerja Dosen, 2025)
In the world of education, we learn many important lessons. Despite this, many Indonesians still lack access to quality education, especially in underserved areas. This shows that they need to be made aware of the importance of education. So that students can actively realize their potential, education is an effort that is deliberately created to provide a conducive learning environment. This includes developing spiritual strength, religion, self-control, personality, intelligence, noble character, and abilities that are beneficial to oneself, society, nation and state. This literature study aims to examine the influence of the personality competence of Islamic Religious Education (PAI) teachers on the formation of morals in various senior high schools (SMA) in Indonesia. In the process of instilling morals in students, the teacher's personality competence is very important, considering that teachers are role models that students can emulate and emulate. This research uses a literature review method by analyzing various relevant scientific sources. It is hoped that the results of this discussion will provide an understanding of the influence of PAI teachers' personality competencies on student morals. The PAI teacher's personality competency acts as an internal driver that influences student behavior and morals. By understanding how these competencies influence us, we can gain valuable insight into improving the quality of education at the Senior High School (SMA) level.